The effect of platelet-rich plasma in bone-tendon integration - ÇETİNEL, ŞULE (WROCLAW MEDICAL UNIV, 2017)
Background. The operative reconstruction of a torn or insufficient anterior cruciate ligament has become a routine surgical procedure in orthopedics. The long-term success of an anterior cruciate ligament reconstruction depends on the ability of the graft to heal adequately in a bone tunnel. Investigators studying reconstructions described healing within a tunnel as osseous ingrowth and incorporation. In particular, helping the healing using autologous material for the best integration process was a new idea that helped us to set up this study. Objectives. The purpose of this study is to show the effect of platelet-rich plasma on bone-tendon healing. Material and methods. Ten New Zealand rabbits were used. The study had 2 groups: (1) a study group including the right extremities of rabbits in which tendon-bone integration was strengthened by platelet-rich plasma and (2) a control group including the left extremities of rabbits in which tendon-bone integration was without platelet-rich plasma. On the 56th day postoperatively, the portion of the distal femur containing the tunnel was amputated following the euthanization process for histological evaluation. Results. In the histological evaluation of the tendon-integrated bone segments with platelet-rich plasma, the integration of tendon in the bone was successful without any necrosis formation in most of the tissues. However, in the control group without platelet-rich plasma, the integration was distorted in many zones and some cystic morphologies were present. Conclusions. The findings of this study showed that using platelet-rich plasma during tendon-to-bone implantation has positive effects histologically. In the literature, many studies are available that have investigated the effect of platelet-rich plasma on anterior cruciate surgery radiologically. However, the histological findings are more reliable than radiological findings because bone-tendon integration is a biological process.
Keywords: platelet-rich plasma; anterior cruciate ligament; tendon; integration; revision surgery; ANTERIOR CRUCIATE LIGAMENT; MORPHOGENETIC PROTEIN-2; GROWTH-FACTORS; FIBRIN GLUE; GRAFT; ENHANCEMENT; TUNNEL; RECONSTRUCTION; AUGMENTATION; PERIOSTEUM